Classroom Management In Improving Learning Effectiveness - Ilfan Tufail; Zainuddin Al Haj Zaini; St. Rodliah (Institut Agama Islam An-Nawawi Purworejo, 2023)
Classroom management is a series of activities that teachers consciously carry out in an effort to create and maintain optimal learning conditions. This study uses qualitative research with a descriptive approach, with data collection techniques through observation, interviews and documentation. To analyze the data used descriptive qualitative method. The results of the study show that class management in improving learning effectiveness at MA Miftahul Ulum, it can be concluded that class management can indeed increase learning effectiveness at MA Miftahul Ulum Besuki, Situbondo and all homerooms and teachers are always working to improve class management so that the student learning process increase may occur.